Heritage studies : stories in the making - Bowe, Meghan (Cambridge Scholars Pub., 2013)
In recent years, heritage has grown by leaps and bounds, beyond the reach of the conservation of monuments and into the realms of economic growth, community development and human rights. But how have shifts in the meaning of ""heritage"" changed its study? And how will heritage continue to evolve in the future? Heritage Studies: Stories in the Making, an edited collection developed from a conference at the McDonald Institute of Archaeology, University of Cambridge, attempts to respond to these ...